2022
DOI: 10.1590/0004-282x-anp-2022-s108
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis

Abstract: Cerebral venous sinus thrombosis (CVT) consists of partial or complete occlusion of a sinus or a cerebral vein. CVT represents 0.5-1% of all strokes and is more frequent in young women. This review discusses particular aspects of CVT diagnosis and management: decompressive craniectomy (DC), anticoagulation with direct oral anticoagulants (DOACs), CVT after coronavirus-disease 19 (COVID-19) and Vaccine-Induced Immune Thrombotic Thrombocytopenia (VITT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…Transverse sinus (44-73%) and superior sagittal sinus (39-62%) have been reported to be the most commonly affected sinuses by thrombosis, and in our study, transverse sinus involvement was 18.7%, and superior sagittal sinus involvement was 43.7% 14 . Ferro JM et al reported that superior sagittal sinus involvement increased the risk of epileptic seizure development 6 .…”
Section: Discussionsupporting
confidence: 65%
“…Transverse sinus (44-73%) and superior sagittal sinus (39-62%) have been reported to be the most commonly affected sinuses by thrombosis, and in our study, transverse sinus involvement was 18.7%, and superior sagittal sinus involvement was 43.7% 14 . Ferro JM et al reported that superior sagittal sinus involvement increased the risk of epileptic seizure development 6 .…”
Section: Discussionsupporting
confidence: 65%